2022
DOI: 10.3390/vaccines10111927
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 among Czech Dentistry Students: Higher Vaccination and Lower Prevalence Compared to General Population Counterparts

Abstract: The restrictions on medical students’ clinical education during the COVID-19 pandemic has affected their professional readiness and often lengthened their training. These negative impacts are often considered a necessary price as clinical education is hypothesized to be associated with a high risk of pandemic spread. This work assesses this hypothesis based on COVID-19 epidemiological data among Czech dentistry students and their comparison to data of the Czech general population of similar age. We addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Additionally, evidence from an Austrian study suggests that HCWs were equally divided about accepting COVID-19 vaccine mandates for the general population [38]. About a third of HCWs were in favor of mandatory vaccinations against COVID-19 in a study from Slovenia, while in a study conducted in the Czech Republic, HCWs supported mandatory COVID-19 vaccines for the general population [39,40]. All three included studies from Italy resulted in similar findings, reporting that most of HCWs supported mandatory COVID-19 vaccinations for the general population [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, evidence from an Austrian study suggests that HCWs were equally divided about accepting COVID-19 vaccine mandates for the general population [38]. About a third of HCWs were in favor of mandatory vaccinations against COVID-19 in a study from Slovenia, while in a study conducted in the Czech Republic, HCWs supported mandatory COVID-19 vaccines for the general population [39,40]. All three included studies from Italy resulted in similar findings, reporting that most of HCWs supported mandatory COVID-19 vaccinations for the general population [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…In the single included study from Cyprus, HCWs were divided on their attitudes towards COVID-19 vaccine mandates [32]. The last three studies from Europe (UK, Poland, and the Czech Republic) showed conflicting results regarding HCWs' acceptance of vaccine mandates for HCWs (acceptance rates: 6-75%) [37,40,57]. A generally supportive attitude was reported in a series of seven studies from the US, while data from two Australian studies revealed that Australian HCWs were divided about accepting COVID-19 vaccine mandates for HCWs [44][45][46][58][59][60][61][62][63].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the participants in our study, 42% reported having been immunized, with the majority of them immunized with two doses. Despite the many questions that have arisen regarding vaccine safety, duration of immunity, and others, students at our university have achieved good immunization coverage, but compared to the students at other European universities, significantly lower [5]. Complete vaccination is essential to achieve a good protective effect.…”
Section: Discussionmentioning
confidence: 91%
“…At the same time, the medical students as a part of the population also were involved in the epidemiological process for transmission of the infection. There are few studies on the prevalence of COVID-19 among medical students [1][2][3][4]5]. Although, during the pandemic, new variants of SARS-CoV-2 have appeared and the severity of infection decreased, the high contagiousness of the virus and the increased risk for working medical professionals, including students training in medical specialties, still remain.…”
Section: Introductionmentioning
confidence: 99%